Ancaman Pidana Mati Bagi Pelaku Tindak Pidana Begal Sebagai Solusi Mengurangi Tingkat Kejahatan Begal di Kota Makassar - Hamzah, Hamzah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2016)
Criminal robber today increasingly made public Makassar City can not perform its activities properly, because it always felt threatened by street actions of the perpetrators. From the research, the crime robber in Makassar more dominant influenced by the desire to emulate after watching a scene or event through electronic media TV has indirectly serving news or violent incidents that occurred in various parts of the country water. The spectacle results become negative for the development of child education which is precisely through such education the children will try to do and practice sees. In sociology called "Society is imitation. Society is always in the process of imitating. When people are fed every day hardness values, rude, people eventually emulate. This statement is supported by data from several actors robber who were interviewed by the author. In addition, the robber occurs due to the persuasion of his friends, The criminal robber never thought a result of this action will be able to bring the perpetrators to deal with the police and cause it to go into bars.